Merozoite surface protein 1 from plasmodium falciparum is a major target of opsonizing antibodies in individuals with acquired immunity against malaria - Jäschke, Anja; Bujard, Hermann; Epp, Christian (Clinical and vaccine immunology, 2017)
Naturally acquired immunity against malaria is largely mediated by serum antibodies controlling levels of blood-stage parasites. A limited understanding of the antigenic targets and functional mechanisms of protective antibodies has hampered the development of efficient malaria vaccines. Besides directly inhibiting the growth of Plasmodium parasites, antibodies can opsonize merozoites and recruit immune effector cells such as monocytes and neutrophils. Antibodies against the vaccine candidate merozoite surface protein 1 (MSP-1) are acquired during natural infections and have been associated with protection against malaria in several epidemiological studies. Here we analyzed serum antibodies from semi-immune individuals from Burkina Faso for their potential (i) to directly inhibit the growth of P. falciparum blood stages in vitro and (ii) to opsonize merozoites and to induce the antibody-dependent respiratory burst (ADRB) activity of neutrophils. While a few sera that directly inhibited the growth of P. falciparum blood stages were identified, immunoglobulin G (IgG) from all individuals clearly mediated the activation of neutrophils. The level of neutrophil activation correlated with levels of antibodies to MSP-1, and affinity-purified MSP-1-specific antibodies elicited ADRB activity. Furthermore, immunization of nonhuman primates with recombinant full-size MSP-1 induced antibodies that efficiently opsonized P. falciparum merozoites. Reversing the function by preincubation with recombinant antigens allowed us to quantify the contribution of MSP-1 to the antiparasitic effect of serum antibodies. Our data suggest that MSP-1, especially the partially conserved subunit MSP-183, is a major target of opsonizing antibodies acquired during natural exposure to malaria. Induction of opsonizing antibodies might be a crucial effector mechanism for MSP-1-based malaria vaccines.
Accepted manuscript posted online 6 September 2017
Gesehen am 26.06.2018